PENGARUH PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNINGTERHADAP HASIL BELAJAR SISWA SUB TEMA PERUBAHAN LINGKUNGAN - Nisa Haya Hanifah; Rais Hidayat; Rini Sri Indrian (STKIP Subang, 2024)
Nisa Haya Hanifah. 037118043. The effect of implementing the project based learning model on learning outcomes for the environmental change subtheme. Thesis. Pakuan University. Under the guidance of Dr. Rais Hidayat, M.Pd. And Rini Sri Indriani, M. Pd. This research aims to determine the effect of the Project Based Learning model on student learning outcomes on the environmental change subtheme. This research was carried out at SD Negeri Rancabungur 01, Bogor Regency, Classes V-A and V-B from May to June, even semester. The N-Gain calculation for the project based learning model is 64 with medium criteria and the N-Gain value for the conventional model is 43 with medium criteria. So the N-Gain in the experimental class with the Project Based Learning model is greater than the conventional class. Researchers also carried out a normality test with the Liliefors test for both normal distribution samples. Then in the hypothesis test there is a tcount of 2.327 which is greater than the ttable of 1.712, indicating that HO (null hypothesis) is rejected and Ha (alternative hypothesis is accepted. Based on the results of the research above, it can be stated that the Project Based Learning model has an influence on learning outcomes for the sub-theme of changing the classroom environment V at SD Negeri Rancabungur 01 Bogor Regency.